Impact of vibration on human body ergonomics: Analyzing the influence of mass, cushion materials, and backrest angles using FEM. - Sharma, Shubham; Kalsi, Sachin; Singh, Jagjit; Singh, Ishbir; Kumar, Raman; Ambati, Vijay Kumar; Alqahtni, Fahad M; Pandey, Shatrudhan (Work, 2026)
Background: Whole-body vibration (WBV) poses significant health risks, including musculoskeletal disorders and discomfort, especially for individuals exposed to prolonged vibrations, such as drivers and industrial operators. This study evaluates the effects of vibration transmissibility on varying human masses, seat materials, backrest angles, and acceleration levels, aiming to inform the design of ergonomic seating systems that enhance safety and comfort in vibration-prone environments. Objective: To assess the impact of vibrations on human subjects with varying masses representative of the 50th and 95th percentile Indian male population in a seated posture. Also, evaluate the influence of different seat cushion materials and the effect of backrest angles on transmitting vibrations through the human body at different acceleration levels. Methods: A comprehensive 4-layered CAD model of a human subject, incorporating skin, muscles, bones, and organs, was developed. Finite Element Method (FEM) analysis was employed to evaluate the transmissibility of vibrations for each condition. Results: The study revealed how variations in backrest angles, seat cushion materials, and acceleration levels affect the transmission of vibrations through the human body. The FEM analysis, coupled with the detailed human model, provided insights into the potential consequences for ergonomics and overall well-being. A slightly reclined backrest angle (10°–15°) can reduce the vertical vibration transmissibility by shifting the body's center of mass and distributing vibration forces more evenly. Also, polyurethane shall provide good comfort and reduce the effect of vibration on human subjects. Conclusions: The findings offer valuable information for designing ergonomic seating solutions and emphasize the importance of protecting human safety and comfort in environments prone to vibrations. This research contributes to developing safer and more comfortable seating arrangements, enhancing individual health and comfort.